Risk communication in the post-COX2 era - Bouder, Frederic (Henry Stewart Talks, 2009)
Health and the media, Public distrust in the pharmaceutical industry, The precautionary principle, Specific precautionary measures, Problems with the precautionary principle, Risk-based decisions, approaches and communication, Voluntary vs. involuntary approach, Natural and technological issues, Control vs. non-control, Familiarity, Effects on reproduction, Impact on children vs. adults, Different individuals perceive risk differently, How best to communicate risk?, Trust, Lessons to be learned